Non-Invasive Imaging of Phosphoinositide-3-Kinase-Catalytic-Subunit-Alpha (PIK3CA) Promoter Modulation in Small Animal Models - Gaikwad, Snehal M.; Gunjal, Lata; Junutula, Anitha R.; Astanehe, Arezoo; Gambhir, Sanjiv Sam; Ray, Pritha (PLOS ONE, 2013)
Activation of the PI3K/Akt pathway, a critical step for survival in cancer cells is often associated with decreased sensitivity to several chemotherapeutic drugs. PIK3CA gene amplification is observed in 16–24% of epithelial ovarian cancer (EOC) patients in conjunction with p53 mutations. A 900 bp long PIK3CA promoter is shown to be negatively regulated by p53 in ovarian surface epithelial cells but the consequence of chemotherapeutic drug treatments on this promoter in ovarian cancer cells is largely unknown. We aim to study the modulation of this promoter by cisplatin using an improved fusion reporter in ovarian cancer cells and tumor xenografts by non-invasive imaging approach. A PIK3CA sensor was developed using a bi-fusion reporter from a newly constructed library of bi- and tri-fusion vectors comprising of two mutant far red fluorescent proteins (mcherry/mch and tdTomato/tdt), a mutant firefly luciferase (fluc2), and a PET reporter protein (ttk). In vivo imaging of mice implanted with 293T cells transiently expressing these bi- and tri-fusion reporters along with respective controls revealed comparable activity of each reporter in the fusion background and fluc2-tdt as the most sensitive one. Repression of the PIK3CA sensor by drugs was inversely proportional to cellular p53 level in a germline (PA1) and in an EOC (A2780) cell line but not in a p53 deficient EOC (SKOV3) cell line. Bioluminescence imaging of tumor xenografts stably expressing the PIK3CA sensor in PA1 and A2780 cells exhibited attenuating activity without any change in SKOV3 tumors expressing the PIK3CA sensor after cisplatin treatment. Sequential mutation at p53 binding sites showed gradual increase in promoter activity and decreased effects of the drugs. These newly developed PIK3CA-fluc2-tdt and the mutant reporter sensors thus would be extremely useful for screening new drugs and for functional assessment of PIK3CA expression from intact cells to living subjects.